Mastering Money: Building Competency in Personal Finance - Dwi Budi Srisulistiowati; Dovina Navanti; Ahdi Mualim; Sri Rejeki (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research examines the relationships between education level, income level, financial behavior, and financial literacy among customers of BNI Pontianak. Findings indicate that education level significantly influences financial behavior and financial literacy, with customers having higher education levels tending to exhibit better financial behaviors and higher levels of financial literacy. Conversely, income level does not significantly affect financial behavior or financial literacy. Furthermore, financial behavior significantly impacts financial literacy, indicating a reciprocal relationship between the two. These findings underscore the importance of education and financial behavior in enhancing customer financial literacy, emphasizing the need for tailored strategies to improve financial understanding and practices for overall financial well-being.